Topics in Anti-Cancer Research: Volume 1 - Atta-ur-Rahman; Zaman, Khurshid (Bentham Science Publishers, 2012)
The Topics in Anti-Cancer Research e-Book series covers important advances on both experimental (preclinical) and clinical cancer research in drug development.Major developments in the fields of oncology are covered including mechanisms, tumor and stem cell biology, metastasis, tumor suppressors, cancer drug targets, drug clinical trials, cellular and molecular pathology, genomics and genetics, diagnostics, translational therapeutics, tumor immunology, and cancer prevention and epidemiology.Topics in Anti-Cancer Research is an essential e-book series for oncologists, pharmaceutical scientists, clinicians, and to researchers in other related disciplines.